New dictionary of biblical theology - Alexander, T. Desmond; Rosner, Brian S. (Leicester, England : Inter-Varsity Press ; Downers Grove, Ill. : InterVarsity Press, 2000)
The New Dictionary of Biblical Theology will quickly establish itself as an essential building block of every library of basic biblical reference books. Building on its companion volumes, the New Bible Dictionary and New Bible Commentary, this work takes readers to a higher vantage point where they can view the thematic terrain of the Bible in its canonical wholeness. In addition, it fills the interpretive space between those volumes and the New Dictionary of Theology. At the heart of this work is an A-to-Z encyclopedia of over 200 key biblical-theological themes such as atonement, creation, eschatology, Israel, Jesus Christ, the kingdom of God, redemption, suffering, wisdom and worship. Students and communicators of the Bible will be well served by articles exploring the theology of each biblical book. And for those interested in the wider discipline of biblical theology, major articles explore foundational issues such as the history of biblical theology, the challenges raised against biblical theology, and the unity and diversity of Scripture. Over 120 contributors drawn from the front ranks of biblical scholarship in the English-speaking world make the New Dictionary of Biblical Theology a work of distinction and a benchmark of evangelical biblical theology at the turn of the twenty-first century. Bibliographies round out all articles, directing readers to research trails leading out of the Dictionary and into crucial studies on every subject. Cross-references throughout send readers through the varied maze of reading pathways, maximizing the usefulness of this volume. Comprehensive, authoritative and easily accessible, the New Dictionary of Biblical Theology is certain to establish itself as an essential resource for students of the Bible and theology. - Publisher.
Part one : Introduction. Biblical theology -- History of biblical theology -- Challenges to biblical theology -- The canon of scripture -- Scripture -- Biblical history -- Exegesis and hermeneutics -- Unity and diversity of scripture -- New Testament use of the Old Testament -- Relationship of the Old Testament and New Testament -- Systematic theology and biblical theology -- Preaching and biblical theology -- Part two : Biblical corpora and books. Genesis to Kings -- Wisdom books -- Prophetic books -- Synoptic Gospels -- Luke-Acts -- The Johannine writings -- Paul -- Articles on individual books -- Part three : Biblical themes.
Includes bibliographical references and index.
Keywords: Bible -- Theology -- Dictionaries